Digitalization of Indonesian Offloading Management Systems from FPSO to Shuttle Tanker - Palippui, Habibi; Kadhafi, Muammar (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2022)
Artificial Intelligence has experienced significant improvements, including its use in sustainable maritime security. This journal discusses the development of information systems that are interconnected and real time providing reports to all parties who need information. Overall, we find that the potential for oil sabotage is always present in the delivery of tankers from FPSO to shuttle tankers. The concept of integrated FPSO offloading management to tankers implies minimizing the potential loss of cargo. At the same time, the intelligent technology most often used to control maritime security is the Automatic Integrated System.